Dephosphorylated uncarboxylated Matrix-Gla-Protein as candidate biomarker for immune-mediated vascular remodeling and prognosis in pulmonary hypertension - R. Tobal; J. Potjewijd; F. de Vries; D. P.C. van Doorn; A. Jaminon; R. Bittner; C. Akbulut; V. van Empel; P. Heeringa; J. Damoiseaux; L. Schurgers; P. van Paassen (Scientific Reports)
Abstract Pulmonary arterial hypertension (PAH) is a disease characterized by pulmonary vascular remodeling. Since dephosphorylated-uncarboxylated Matrix Gla-Protein (dp-ucMGP) is associated with cardiovascular mortality in systemic sclerosis, a disease associated with PAH, and immune-system involvement in PAH is increasingly recognized, we investigated the relationship between dp-ucMGP, vascular remodeling and soluble immune-checkpoint proteins in PAH. This prospective cohort study included patients with idiopathic (I)PAH, connective tissue disease (CTD)-PAH, chronic thrombo-embolic PH (CTEPH) and CTD patients without PAH. Patients with IPAH and CTD-PAH were stratified by clinical signs of immune-mediated inflammatory disease (IMID). We measured dp-ucMGP plasma levels, soluble immune-checkpoint proteins (sICPs), and vascular smooth muscle cell (iVSMC) calcification. We found elevated dp-ucMGP levels in all PAH subtypes and CTD patients compared to healthy controls. PAH patients showed increased iVSMC calcification, but no direct correlation was found with dp-ucMGP. IMID-PAH patients had higher dp-ucMGP levels than non-IMID PAH patients. dp-ucMGP correlated with several sICPs in both IPAH and CTD patients; multiple sICPs were elevated in IMID PAH patients. High dp-ucMGP levels in IPAH patients were associated with worse survival. Our findings suggest dp-ucMGP as a potential biomarker of immune-mediated vascular remodeling in PAH. Hence, dp-ucMGP, could help identify PAH patients who might benefit from immunosuppressive therapies.